OPTIMIZATION OF THE GENERAL ELECTION SUPERVISORY BODY IN ENSURING THE FULFILLMENT OF THE RIGHTS OF DISABILITIES - Pawestri, Aprilina; Akbar, Wahyu Nurdin; Rohmah, Maimunatur (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
People with disabilities have physical, intellectual, mental and sensory limitations which may cause them to experience obstacles in carrying out their activities. One of them is related to fulfilling the right to vote in general elections. This has implications for the limited participation rate of voters with disabilities. The General Election Supervisory Agency (Bawaslu), as one of the election organizers, has the main task in the field of supervision. Can play a bigger role in efforts to increase participation of voters with disabilities. Contributed articles related to issues regarding the implementation of the voting rights of persons with disabilities and optimizing the role of Bawaslu in fulfilling the rights of persons with disabilities, focusing on Sampang and Bangkalan Regencies as research locations. The methodology used is empirical/sociological legal research. With data collection techniques through interviews with relevant respondents. The research results show (1) The implementation of the right to vote for persons with disabilities in general elections has not been fully realized, participation is still limited. (2) Optimizing the rights of persons with disabilities in general elections carried out by Bawaslu of Sampang and Bangkalan Regency, namely conducting outreach to disabled voters together with the Indonesian Association of Disabled People (PPDI) as well as carrying out participatory supervision, coordinating with the General Election Commission (KPU) at every stage of the election and establishing cooperation with local governments.